A multi-objective placement of phasor measurement units using fuzzified artificial bee colony algorithm, considering system observability and voltage stability - Arul jeyaraj, K.; Rajasekaran, V.; Nandha Kumar, S.K.; Chandrasekaran, K. (Journal of experimental & theoretical artificial intelligence, 2016)
This paper presents Multi-objective Optimal Placement of Phasor measurement units (MOPP) to improve the performance of power system monitoring and control. It is proposed for achieving complete observability with a minimal number of phasor measurement units (PMUs) and maximising the voltage stability level of the system, simultaneously. As the above mentioned objectives are conflicting in nature, a fuzzified binary artificial bee colony algorithm is considered to solve the MOPP problem to offer a good tradeoff solution between the competing objectives. Here, fuzzy membership for each objective function is designed and proposed to decide the best solution of MOPP problem. Initially, weak buses are identified using the fast voltage stability index calculation for their close and reliable monitoring. This is done in order to prevent the outage of these buses. The conventional rule is used to minimise the number of PMUs and a new rule is proposed to maximise both the observability and voltage stability levels of the system. The efficiency of the artificial bee colony method is validated on IEEE 14, 30 and 57 bus test systems and it is verified by comparing the performance of proposed method with earlier works.